Inflation threshold effect on economic growth in turkey1 - Esen, Ö.; Aydin, C.; Aydin, R. (ASERS Publishing House, 2016)
In this study, the role of inflation threshold effect on economic growth has been investigated for Turkey in the 2002:Q1 – 2015:Q1 period. At the first stage, inflation threshold value has been detected. After that, inflation-economic growth relation has been examined using threshold autoregressive (TAR) model. Results indicate that there is a nonlinear relationship between inflation and growth rate; the threshold for the influence of inflation on economic growth is 8.89%; and an inflation rate above this threshold has a negative influence on economic growth while an inflation rate below this threshold has a positive influence on economic growth. In this regard, it is important to achieve sustainable growth, which plays a crucial role in increasing the efficiency of implemented monetary policies and assuring stability. Therefore, political and economic decision-makers should not ignore the concept of threshold within the scope of monetary policy while determining the target inflation rate in their efforts to deal with inflation. © 2017, ASERS Publishing House. All rights reserved.
Keywords: Economic growth; Inflation target; Inflation threshold; Threshold autoregressive model